Multi-analytical residue analysis of the trihedral adze: a case study for the introduction of new methodologies in boreal forest archaeology - Cook, Russell (My University, 2015)
This thesis aims to evaluate the use of multi-analytical residue analysis in archaeological investigations in the Boreal Forest through the examination of a specific artifact class – the trihedral and related adze tool types recovered from the Thunder Bay District and surrounding regions. The trihedral adze has not yet been confidently attributed to any specific cultural period in the pre-history of the Thunder Bay region. It is hoped that a detailed analysis of this artifact type may provide insight into tool use, and allow it to be attributed to a specific culture. This work also addresses the feasibility of the analytical approach. Methods employed include microscopy, biochemical and analytical chemical techniques with the research being approached using the Archaeological Biomarker Concept and the Artifact as Site Concept. Combining these approaches involves examining the artifact independent of the site using the methods noted above to determine the chemical nature of any residues, thereby allowing for an identification of residue source. The methods employed were successful in identifying tool use. The findings of this research indicate the adzes were employed in the processing of conifer trees, at least some of which were treated with a controlled use of fire. This practice is consistent with the production of dugout canoes. At least one secondary tool use as a butchering tool was noted on one artifact. In addition to determining tool use these findings allow for the determination of site activities at archaeological sites which have not yet been excavated.
Keywords: Trihedral adze; Deglagication; Hydrological and environmental history of Northwestern Ontario; Paleohydrology; Archaeological biomarker concept